Similarity in school textbooks on natural sciences for the primary school level : an analysis of teaching and apprenticeship of botany in the last century in Portugal (1900-2000) - Guimarães, Fernando (2009)
By analyzing school textbooks, we evidenced that Botany contents used for the teaching of Sciences cannot be isolated from both educational and curricular policies adopted in Portugal during the 20th century. Within schools, textbooks are important tools to conform shapes and contents applied in the pedagogical knowledge. The articulation of aspects related to the sequence and pace of knowledge transmission has momentous pedagogical and didactic objectives, which are made possible through properly devised activities and evaluation mechanisms for such acquisitions. With this perspective in mind, such objectives can allow us to know the subjacent pedagogical and curricular ideology, as well as the way through which the learning and apprenticeship process is understood. Such process takes place within classrooms and plays an important role for teachers and students. The present study, based upon the PhD thesis on Children Studies (Botany within school textbooks for Primary and Basic teaching levels [1st cycle] in the 20th century in Portugal), aims to analyze the importance Botany is given in Portugal in school textbooks that cover Natural Sciences for Primary School students in the last century. Our attempt to know how botanical topics were differently adopted throughout time in the school textbooks relied on 11 principles: Shape; Kingdoms; Classification; Organs; Root; Stem; Leaf; Flower; Fruit; Reproduction; and Dimension. Such appreciation, based upon a methodological approach that analyses content, upon the establishment of a posteriori categories, and upon the cluster analysis with dendrogram build-up, contributes to encounter primary sources related to content, which engulf curricular, pedagogical and didactic orientations. These orientations bear educational, curricular and didactics policies, as well as educational and scientific values suggested herein. Results have shown that despite the variation on terminology found in school textbooks (including the ones from Natural Sciences, Natural-Geographic Sciences, Physical and Social Environment, and Environment Studies), various aspects evolve, such as a decreasing level of complexity, similarity and specificity relationships amongst school textbooks, and the maintenance of Botany content.